Automated closed volume reduction process for apheresis stem cell grafts: From development to clinical implementation. Issue 9 (19th July 2022) - Howell, Anita; Letcher, Brenda; Murphy, Kelly; Elmoazzen, Heidi; Petraszko, Tanya; Acker, Jason P.; Pineault, Nicolas; Holovati, Jelena L.
Abstract: Background: Collection of HPC by apheresis (HPC‐A) can sometimes result in higher collection volumes, increasing the dimethyl sulfoxide (DMSO) volume infused into patients and the space requirements in liquid nitrogen freezers. Volume reduction prior to the addition of cryoprotectant is an efficient means to reduce the DMSO load infused into patients and to optimize freezer storage space. Study Design and Methods: To implement a closed semi‐automated volume reduction process, a method was developed to produce leukocyte‐rich mock apheresis products using buffy coats derived from whole blood collections. The mock HPC products were then used to measure the efficiency and reliability of the semi‐automated process over a range of volumes and cell concentrations. The resulting data was used to support the implementation of the process with concurrent monitoring. Results: A closed, semi‐automated volume reduction process resulted in recoveries of over 93% and 91% of white blood cells and CD34 + cells with no significant loss of product viability or potency. Mean doses of CD34 + and CFU infused per kilogram recipient body weight were 4.0 ± 1.1 × 10 6 /kg and 4.2 ± 1.7 × 10 5 /kg, resulting in no delays in median time to neutrophil and platelet engraftment, significant increase in adverse reaction or nonconformances. Discussion: The effectiveness outcomes of the first Canadian experience in the implementation of a closed semi‐automated volume reduction system in the processing of HPC‐A products for autologous transplant have met the predetermined acceptance criteria, supporting its use in a stem cell manufacturing laboratory compliant with good manufacturing practice regulations.